PEMILIHAN BAHAN PUPUK ORGANIK UNGGULAN DALAM SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE WEIGHTED PRODUCT - Heroe Santoso; Raisul Azhar; Suriyati Suriyati; Melati Rosanensi; I Made Yadi Dharma; Husain Husain; Fathurrahman Fathurrahman (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
Organic fertilizer is a type of fertilizer that comes from natural ingredients that contain organic materials, such as plant, animal or other organic waste. Organic fertilizer naturally contains essential nutrients for plants, such as nitrogen, phosphorus, potassium, micronutrients and beneficial organic materials. Organic fertilizers have experienced significant development in recent years. Increased awareness of the importance of sustainable and environmentally friendly agriculture has encouraged the use and development of organic fertilizers. Meanwhile, organic fertilizer can be produced through composting, fermentation or decomposition of organic materials. To be able to produce superior and quality fertilizer products, of course you must choose superior or quality product ingredients. Sources of organic material can be goat kohe, effective microorganism 4 (EM4), bamboo leaf waste, chicken manure waste, burnt husks, cocopeat, coconut fiber. This research aims to create a decision support system using the weighted product (WP) method. WP is a popular multi-criteria analysis decision and is a multi-criteria decision making method. The choice of the weighted product (WP) method is also based on its ability to provide optimal solutions in the ranking system. The choice of this method is also based on the computational complexity which is not too difficult so that the time required to produce calculations is relatively short